Schoology-based e-learning: The impact on concepts understanding and mathematical communication abilities - Yolla Yulia Astuti Yuningsih; Farida Farida; Dona Dinda Pratiwi (CV FOUNDAE, 2021)
The purpose of this study (1) To find out the effect of schoology-based e-learning media on concepts understanding and mathematical communication abilities.(2) Knowing the effect of schoology-based e-learning media on the ability to understand concepts. (3) Knowing the effect of schoology-based e-learning media on mathematical communication ability. The study used a quasi-experimental design with Posttest-OnlyControlDesign. Random sampling technique with a population of 259 students of class X MAN 1 East Lampung. The sample of the experimental class is 30 students, and the control class is 30. Collecting data in the form of tests, interviews, and documentation. The data analysis technique used is One-way Multivariate Analysis of Variance test with a significance level of 5%. The result of the study is (1) There is an effect of schoology-based e-learning media on concepts understanding and mathematical communication abilities, the F value is 3,821 with a significance of 0,042. (2)There is an effect of schoology-based e-learning media on the ability to understand concepts with an F value of 126.761. (3) There is an effect of schoology-based e-learning media on mathematical communication ability with an F values of 19.532. it can be concluded that schoology-based e-learning media is effective in increasing the concepts understanding and mathematical communication abilities. However, in this study, it has not emerged what learning model is used in applying the schoology media. Hence, when measuring mathematical communication ability, students only measure in the form of written communication (answers to description questions). Further research can be done by showing the use of appropriate learning models for schoology media. Also, the measurement of mathematical communication ability must also be considered in other forms, namely during discussion forums in schoology